Treatment of persistent atrial fibrillation using phased radiofrequency ablation technology. (August 2011) - Deneke, Thomas; Mügge, Andreas; Balta, Osman; Horlitz, Marc; Grewe, Peter H; Shin, Dong-In
A novel ablation system consisting of a duty-cycled phased radiofrequency generator and multielectrode mapping and ablation catheters has been introduced to provide ablation therapy in patients with symptomatic atrial fibrillation (AF). Contiguous lesions may be created using anatomically designed ablation catheters maneuvered under fluoroscopic guidance without the use of a 3D electroanatomic mapping system. In addition to pulmonary vein isolation using a circular, decapolar ablation catheter, an ablation strategy targeting complex fractionated atrial electrograms can be performed using two supplemental multiarray catheters specifically designed for ablation at the left atrial septum and within the left atrial body. Procedural times for treating persistent AF using phased radiofrequency are reported as being between 2 and 2.5 h. Freedom from AF ranges between 33 and 75% after a single procedure, which is comparable to other conventional ablation approaches (utilizing electroanatomic mapping). Additional studies in larger patient numbers are needed to understand the long-term maintenance of results and potential adverse effects of the technology.